2003
DOI: 10.1073/pnas.0530276100
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interaction modulated by allelic heterogeneity in inflammatory diseases

Abstract: CARD15 is a major susceptibility gene for a frequent multifactorial chronic inflammatory bowel disorder, Crohn disease (CD). By using NF-B activation assays, the cytosolic CARD15 was shown to efficiently detect bacterial peptidoglycan (PGN), reminiscent of the PGN recognition protein surveillance mechanism in Drosophila. The 3 CD-associated variants and 13 additional variants carried by CD patients demonstrated impaired PGN-dependent response revealing null, hypomorphic, or dominant-negative properties. Quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
219
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(237 citation statements)
references
References 35 publications
16
219
2
Order By: Relevance
“…Consistent with our functional data, I352S is the only polymorphism among all identified in the NACHT domain of NLRP2 that localizes in a position aligned with a disease-associated variation (E441K in NOD2) in either NLRP3 or NOD2 proteins. It has been shown that the E441K change has an impact on the NOD2-mediated activation of NF-B in response to bacterial peptidoglycan and is considered a rare polymorphism associated with Crohn's disease (38). Taking into account the complex control on the activation of NF-B and the increasing number of proteins involved, analyses of deleterious or activating polymorphisms in candidate genes will be needed to decipher their contribution to chronic inflammatory disorders or autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our functional data, I352S is the only polymorphism among all identified in the NACHT domain of NLRP2 that localizes in a position aligned with a disease-associated variation (E441K in NOD2) in either NLRP3 or NOD2 proteins. It has been shown that the E441K change has an impact on the NOD2-mediated activation of NF-B in response to bacterial peptidoglycan and is considered a rare polymorphism associated with Crohn's disease (38). Taking into account the complex control on the activation of NF-B and the increasing number of proteins involved, analyses of deleterious or activating polymorphisms in candidate genes will be needed to decipher their contribution to chronic inflammatory disorders or autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…51 Nod1, in contrast, has a narrow specificity and recognizes only DAP-type PG, which constitutes a signature of most Gram-negative bacterial PGs. 43 Nod1 detects efficiently the naturally occurring muropeptide GM-L-Ala-DGlu-mesoDAP, but the minimal motif found to activate human Nod1 is the dipeptide D-Glu-mesoDAP.…”
Section: Nods and Pg Motifsmentioning
confidence: 99%
“…63 Recurrent mutations in the central NACHT domain from NOD2 have been linked with these diseases. 109 Compared to wild-type NOD2, the most frequently found mutation, R334Q, leads to increased basal NF-kB activation, in the absence of ligand, 51 and further increased NF-kB activation upon MDP stimulation. 55 Noticeably, Crohn's disease and BS are both characterized by a granulomatosis disorder, but mutations in NOD2 associated with these diseases have opposite effects on the NF-kB activation.…”
Section: Nod2mentioning
confidence: 99%
“…These studies suggested that RICK is involved in TLR signaling. However, many preparations of bacterial components contain Nod1-and Nod2-stimulating molecules (4,5,7,15,16) and the presence of such contaminants could also explain reduced TLR signaling in RICK-deficient macrophages. In the present report, we have studied the role of RICK in TLR signaling in macrophages and in the animal.…”
mentioning
confidence: 99%